Study on the Shear Characteristics of the Frozen Soil–Concrete Interface at Different Roughness Levels - Ming Xie; Mengqi Xu; Fangbo Xu; Zhangdong Wang; Lie Yin; Xiangdong Wu (Buildings)
The shear characteristics of the frozen soil–concrete interface are core parameters in frost heave resistance design in cold-region engineering, and the influence mechanism of interface roughness on these characteristics is not clear. In this study, the regulatory effect of different roughness levels (R-0 to R-4) on the interfacial freezing strength was quantitatively analyzed for the first time through direct shear tests, and the evolution characteristics of the contribution ratio of the ice cementation strength were revealed. The results show that the peak shear strength of the interface increases significantly with the roughness (when the normal stress is 400 kPa and the water content is 14%, the increase in R-4 is 47.7% compared with R-0); the ice cementation strength increases synchronously and its contribution ratio increases with the increase in roughness. Although the absolute value of the residual strength increase is small, the relative amplitude is larger (178.5% increase under the same working conditions). The peak cohesion increased significantly with the roughness (R-0 to R-4 increased by 268.6%), while the residual cohesion decreased. The peak and residual internal friction angle increased slightly with the roughness. The study clarifies the differential influence mechanism of roughness on the interface’s shear parameters and provides a key quantitative basis for the anti-frost heave design of engineering interfaces in cold regions.